Global food security impacts of extreme weather events and occurrence of breadbasket failures - Martin, Will; Nia, Reza; Vos, Rob (International Food Policy Research Institute, 2025)
Agricultural yield shocks are frequently correlated across countries and much of the recent literature concludes that both the volatility of shocks and the extent of correlations across countries are likely to increase substantially with climate change. Given this background, it seems important to consider the potential impacts of large, synchronized yield shocks in both developing and developed countries. These shocks are examined using IFPRI’s MIRAGRODEP model and the linked POVANA household models to assess the impacts on real incomes, food prices, poverty and food insecurity. The results of a 25% reduction in productivity in South Asia and Eastern and Southern Africa are compared with a similar productivity reduction in Europe and North America. The results make clear that the adverse impacts on global poverty and food security are much more severe when the shock originates in developing countries. The results point to a need for quite different policy responses in the case of a multiple breadbasket failure arising in the global south, rather than—like the three most recent food crises—in the global north.